Helping 300 million small-scale farmers to the path to resilience through the Global Commission on Adaptation Report - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
CCAFS informed the food security work of the Global Commission on Adaptation by co-authoring the food security chapter in the GCA Report as well as Bruce Campbell, CCAFS Program Director, co-leading the Food SecurityAction Track.